Intellectual humility and interreligious dialogue between Christians and Muslims - Schillinger, Jamie (Islam and Christian-Muslim relations, 2012)
This article addresses the question of whether Christians and Muslims mean the same thing when they speak of humility and the role that attitude might play in Christian-Muslim dialogue. To restrict the focus, current scholarly reflection on humility and its role in dialogue is analyzed in relation to ‘classic’ accounts of the attitude from each tradition, namely Abū Ḥāmid al-Ghazālī's and Bernard of Clairvaux's. On the basis of the analysis and argument, two conclusions are advanced: first, there is an underlying structure common to Christian and Muslim accounts of humility, while there are also differences resulting from theological emphases; second, Christian and Muslim humility have valuable roles to play in Christian-Muslim dialogue, though they are different from the roles envisioned by prominent Christian and Muslim advocates of dialogue. A particular example of confusion in contemporary discussions, it is suggested, is the putative necessary connection between humility and an inclusivist attitude of acceptance toward the religious ‘other’. The article argues that humility can be exemplified by religious exclusivists and that, while it is an aid to better negotiating debates over exclusivism and inclusivism, it cannot resolve them.